Prevalence and Predictors of Depression, Anxiety, and Stress Symptoms among Jordanian University Students Amid COVID-19 Pandemic - Samar Bakkar; Manar AlAzzam; Shaher Hamaideh; Asem Abdalrahim (Jordan University of Science and Technology, 2024)
Background: The COVID-19 pandemic has led to increased rates of depressive, anxiety, and stress symptoms. University students have been particularly affected by these psychological consequences due to the pandemic and its accompanying precautions. Objective: This study aimed to assess the prevalence and predictors of depressive, anxiety, and stress symptoms among Jordanian university students amid COVID-19 pandemic. Method: Data was collected through a survey from Jordanian university students. The survey included a self-reported questionnaire that is composed of socio-demographic variables and the Arabic version of the Depression, Anxiety, and Stress Scale (DASS-21). Results: The mean total scores for depressive, anxiety, and stress symptoms were 18.91, 18.04, and 20.71 respectively, indicating the presence of these psychological issues among university students during the pandemic. Psychological problems, parents diagnosed with mental illness, living arrangements, and academic year explained 25.6% of the variation in depressive symptoms. Academic year, living arrangements, specialization, GPA, and gender accounted for 25.9% of the variation in anxiety symptoms. Parents' diagnosed with mental illness, specialization, marital status, and GPA explained 22.3% of the variation in stress symptoms. Conclusion: Adequate intervention is necessary to support these students, and it is essential for faculty members and administrators to provide appropriate psychological assistance. Additionally, national strategies should be implemented to raise awareness among Jordanian university students about the symptoms of depression, anxiety, and stress.